An O(| V| 2) algorithm for single connectedness - Khuller, Samir (Information processing letters, 1999)
A directed graph G=( V, E) is said to be singly connected if u⇝v implies that there is at most one simple path from u to v for all vertices u, v∈ V. In this paper we design an algorithm to test a graph for being singly connected that takes O(| V| 2) steps.